PERBEDAAN PENGETAHUAN TENTANG GANGGUAN PEMUSATAN PERHATIAN DAN HIPERAKTIVITAS PADA ORANG TUA ANAK GPPH - Ainur Rohmah, Faridah; Listiyanti Widuri, Erlina (Universitas Ahmad Dahlan, 2010)
The purpose of this research was to investigate the differences of the knowledge of ADHD between before and after group discussion. The subjects were parents of ADHD children. They volunteered to participate in the research. There were 8 parents. This study performed by with pretest and post-test control measurement toward scale of knowledge of ADHD. The data were analyzed quantitatively and qualitatively. The quantitative data were analyzed with t-test. The data from the observational record and self report from the subjects were analyzed qualitatively. The result shows that: there is no difference in knowledge of ADHD between before and after group discussion (t=-0.499, p=0.633 (p>0.05)).